2015
DOI: 10.1523/jneurosci.0684-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Losing Control: Excessive Alcohol Seeking after Selective Inactivation of Cue-Responsive Neurons in the Infralimbic Cortex

Abstract: Loss of control over drinking is a key deficit in alcoholism causally associated with malfunction of the medial prefrontal cortex (mPFC), but underlying molecular and cellular mechanisms remain unclear. Cue-induced reinstatement of alcohol seeking activates a subset of mPFC neurons in rats, identified by their common expression of the activity marker cFos and comprised of both principal and interneurons. Here, we used cFos-lacZ and pCAG-lacZ transgenic rats for activity-dependent or nonselective inactivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
153
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(164 citation statements)
references
References 61 publications
10
153
1
Order By: Relevance
“…Moreover, our findings support the possibility that rather than forming a new memory trace as in the regular counterconditioning procedure, counterconditioning administered during reconsolidation led to incorporation of the aversive information into the original memory trace, so that the retrieved cue-cocaine memory was reconsolidated as a cue-aversion memory, and therefore the reinstatement of cocaine-seeking behavior was prevented. Nonetheless, the notion that the memory was replaced is yet to be shown Prevention of drug relapse by memory replacement K Goltseker et al directly in the future using ensemble/engram procedures (Cruz et al, 2013;Pfarr et al, 2015). Interestingly, several studies have recently shown that flipping the order of events in the retrieval-extinction procedure, that is, retrieving the memory after, rather than before extinction training, can prevent relapse in a similar manner to post-retrieval extinction (Baker et al, 2013;Millan et al, 2013), suggesting that the mechanisms underlying this procedure are not necessarily reconsolidation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our findings support the possibility that rather than forming a new memory trace as in the regular counterconditioning procedure, counterconditioning administered during reconsolidation led to incorporation of the aversive information into the original memory trace, so that the retrieved cue-cocaine memory was reconsolidated as a cue-aversion memory, and therefore the reinstatement of cocaine-seeking behavior was prevented. Nonetheless, the notion that the memory was replaced is yet to be shown Prevention of drug relapse by memory replacement K Goltseker et al directly in the future using ensemble/engram procedures (Cruz et al, 2013;Pfarr et al, 2015). Interestingly, several studies have recently shown that flipping the order of events in the retrieval-extinction procedure, that is, retrieving the memory after, rather than before extinction training, can prevent relapse in a similar manner to post-retrieval extinction (Baker et al, 2013;Millan et al, 2013), suggesting that the mechanisms underlying this procedure are not necessarily reconsolidation mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that these activated neurons are cholinergic interneurons that comprise of ϳ2% of dorsal striatum neurons (Graybiel, 1995). There is evidence that cholinergic interneurons are involved in associative learning and reward processing (Pisani et al, 2007), are strongly excited during movement (Benhamou et al, 2014), and their activity correlates with the phasic activity of substantia nigra pars compacta dopamine neurons (Morris et al, 2004). A question for future research is whether the Fos-positive neurons in DMS that do not coexpress dopamine receptors play a role in the incubation of methamphetamine craving.…”
Section: Role Of Dorsomedial Striatum Dopamine and Neuronal Ensemblesmentioning
confidence: 99%
“…Daunorubicin also inhibits calcium-dependent action potentials in a reversible manner (Engeln et al, 2016). Studies using the Daun02 inactivation procedure demonstrated causal roles of neuronal ensembles in different brain areas in context-induced reinstatement of cocaine and heroin seeking (Bossert et al, 2011;Cruz et al, 2014), incubation of heroin and nicotine craving (Fanous et al, 2012;Funk et al, 2016), and alcohol seeking and taking, and withdrawal symptoms (Pfarr et al, 2015;de Guglielmo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Maladaptive behavioral patterns toward alcohol (e.g., compulsive drinking) have been hypothesized to result from the lasting overactivation of specific neuronal ensembles (Hebb, 1949) in the extended amygdala (George et al, 2012;Lee et al, 2015) that mediate the negative emotional states of alcohol withdrawal and encode memories and motivation that are associated with alcohol-related cues (Barak et al, 2013). Numerous studies have identified a key role for the central nucleus of the amygdala (CeA) in alcohol drinking and alcohol dependence (Wrase et al, 2008;Koob and Volkow, 2010;Gilpin et al, 2015). Multiple neuropeptide and neuromodulator systems appear to be dysregulated in alcohol dependence and they appear to converge on GABA circuitry in the CeA to produce excessive alcohol drinking and the negative emotional symptoms of alcohol abstinence (Roberto et al, 2004;Weiner and Valenzuela, 2006;Roberto et al, 2010;Gilpin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified a key role for the central nucleus of the amygdala (CeA) in alcohol drinking and alcohol dependence (Wrase et al, 2008;Koob and Volkow, 2010;Gilpin et al, 2015). Multiple neuropeptide and neuromodulator systems appear to be dysregulated in alcohol dependence and they appear to converge on GABA circuitry in the CeA to produce excessive alcohol drinking and the negative emotional symptoms of alcohol abstinence (Roberto et al, 2004;Weiner and Valenzuela, 2006;Roberto et al, 2010;Gilpin et al, 2015). However, it is unclear whether the CeA as a whole is critical for the manifestation of alcohol dependence or if a discrete popula-tion of neurons in the CeA is required for excessive alcohol drinking.…”
Section: Introductionmentioning
confidence: 99%